Comparison of Magnesium Sulfat Gargle and Ketamine Gargle on The Incidence of Sore Throat and Cough After Extubation - Arianto, Ardana Tri; Santosa, Sugeng Budi; Anindita, Anindita (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2022)
Background : Postoperative sore throat (POST) or postoperative sore throat is one of the most common complications in patients receiving endotracheal intubation. The incidence of sore throat is reduced by administering mouthwash analgesics. The purpose of this study was to determine the difference in the effectiveness of magnesium sulfate gargle and ketamine gargle on the incidence of sore throat and cough after endotracheal extubation.Methods : The research was conducted at the Central Surgical Installation of RSUD Dr. Moewardi Surakarta, started in August 2020. This study is an experimental double-blind randomized control trial in patients undergoing general anesthesia after endotracheal extubation. Mann Whitney U test was used to process the data. The research group was divided into two groups, namely magnesium sulfate gargle (M) and ketamine gargle (K).Results : This study found a significant difference in sore throat when using magnesium sulfat gargle and ketamine gargle on the NRS scale. From the results of the study, there was a significant difference between magnesium sulfate and ketamine gargle at NRS 1 (p = 0.01) and NRS 6 (p = 0.022). In the incidence of cough, there were 7 patients in the magnesium sulfat group who had cough (30.4%) and 7 patients in the ketamine group who had cough (30.4%), the statistical test got p = 1,000 (p> 0.050).Conclusion : There is a significant difference in the incidence of sore throat which is lower in the administration of magnesium sulfate gargle compared to ketamine gargle and there is no significant difference between the administration of magnesium sulfate gargle and ketamine gargle on the incidence of cough after endotracheal extubation.